Physicochemical, Thermomechanical, and Swelling Properties of Radiation Vulcanised Natural Rubber Latex Film: Effect of Diospyros peregrina Fruit Extracts. (13th May 2013) - Hossain, Kazi Md Zakir; Sharif, Nashid; Dafader, N. C.; Haque, M. E.; Chowdhury, A. M. Sarwaruddin
Abstract : A range of radiation vulcanised natural rubber latex (RVNRL) films were prepared using various concentrations of aqueous extracts of mature Diospyros peregrina fruit, which acted as a cross-linking agent. The surface of the RVNRL films exhibited an aggregated morphology of the rubber hydrocarbon with increasing roughness due to increasing fruit extract contents in the latex. An improvement in tensile strength, tensile modulus, and storage modulus of RVNRL films was observed with the addition of fruit extracts compared to the control film due to their cross-linking effect. The glass transition (T g ) temperature of all the RVNRL films was found to be at around −61.5°C. The films were also observed to be thermally stable up to 325°C, while the maximum decomposition temperature appeared at around 375°C. The incorporation of fruit extracts further revealed a significant influence on increasing the crystallinity, gel content, and physical cross-link density of the RVNRL films.